Failure Mechanism Analysis and Life Modeling of Railway Electrical Contact under the Environmental Stress - LI Wenhua; GUAN Xin; ZHOU Lulu; WANG Liguo (机车电传动)
The main environmental factors affecting the normal operation of the railway electrical contacts were analyzed, and the failure mechanism of the contacts under temperature and vibration stress was studied. The temperature rise of the contacts generated by the vibration friction and current was considered synthetically. The micro morphology of the contact surface and the fatigue damage theory were integrated into the generalized Erying model and then the model of the relationship between temperature, vibration stress and life was established. The results showed that the model could reflect the relationship between the environmental stress, the contact morphology and the life.